Natural products for kidney disease treatment: Focus on targeting mitochondrial dysfunction - Huang, Jiewu; Liang, Ye; Zhou, Lili (Frontiers in Pharmacology, 2023)
Kidney is a key organ in human body to excrete toxins and sustain the balance of water and electrolyte. In its embryonic development and disease evolution, kidney endures enormous changes in macrostructure, accompanied by a variety of microstructural histological features of glomerular formation and sclerosis, tubule elongation and atrophy, interstitial establishment and fibrosis extension. All of these rely on the frequent occurrence of cell death and growth. Notably, to overcome the disease, some cells try to regenerate through self-repair or progenitor cell differentiation. However, the underlying signal mechanisms of kidney development and regeneration have not been elucidated. Recently, Wnt signaling has been noticed by scientists. Although as a well-known development signal under the spot light, the role of Wnt signaling in kidney development and regeneration is still not well-recognized. In this issue, we generally review the important role of Wnt signaling in kidney embryonic development and tissue repair of cell division, and progenitor cell differentiation after injury. Moreover, we briefly highlight advances in the understanding of the pathogenic mechanisms of Wnt signaling in mediating cellular senescence in kidney parenchymal and stem cells, an irreversible arrest of cell proliferation to resist repair and regeneration. We also highlight the therapeutic targets against Wnt signaling in kidney diseases and provide important clues for clinical strategies.